A conceptual model for wind and debris impact loading of structures due to tornadoes. Issue 175 (April 2018) - Baker, C.J.; Sterling, M.
Abstract: This paper presents a novel conceptual design framework which takes into account the direct wind loads and pressure loads acting on a structure due to the passing of a tornado. Furthermore, for the first time, the potential damage due to debris impact has been incorporated enabling a holistic assessment of structural loading to be considered. The model is built on a recently developed wind and pressure field model that captures the main features of tornadoes, which is used to generate a large number of tornado wind and pressure field realisations from which values of particular load effects can be determined. A cumulative distribution function of load effect is thus derived, which can be combined with tornado climatology probabilities to determine load effects at a particular risk level. This use of this framework is illustrated through two examples – the direct wind and pressure loads on a low-rise portal frame structure, and the debris loads on a medium rise rectangular structure. Highlights: A design framework for calculating wind loads in tornadoes. Framework takes into account direct wind loading, pressure loading and debris loading. The use of simple expressions for velocities and pressures in a statistical framework. Output consists of CDF for direct wind loading, pressure loading and debris impact loading. Enables rational risk based design to take place.